Impact of Fertilizers on Surface Water Quality in UTHM - AHMAD HAKIMI AIDIL BIN ABDUL SHUKOR; MAT DAUD, AZRA MUNIRAH (Recent Trends in Civil Engineering and Built Environment, 2023)
Widespread application and excessive usage of fertilizers in agricultural sectors have highly impact the surface water quality and further deteriorate the nearby waterbody. The objective of the research is to identify the composition of fertilizers used in the fertilizing activities in G3 lake, UTHM and to identify the impacts of fertilizers on surface water quality in term of pH, COD and AN. Two methods that being used to obtain result which are in-situ measurements and laboratory measurements regarding to the APHA standard. The in-situ measurement using DO meter and depth sounder while laboratory measurement using IC, AAS, DR6000 and pH meter. The water samples that taken from the lake using composite grab sample method which the water samples stored in HDPE bottles after three days of fertilizing activities. G3 lake pH value dropped while the concentration of COD and AN increased due to the acidity of the fertilizers and the composition of fertilizers being dissolved after rainfall events. In conclusion, deterioration of water quality in G3 lake is not only caused by the fertilizing activities but also by various other aspects. However, sampling procedure can be carried out weekly for three weeks in order to observe more on water quality degradation by the fertilizing activities.